Pengaruh Integritas, Independensi dan Etika Auditor Terhadap Kualitas Audit Internal - Mohamad Ikram Bin Holan; Siti Pratiwi Husain; Nurhayati Panigoro; Titi Umi Kalsum Hulopi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Abstract, The research was conducted to determine: 1. To determine the effect of Auditor Integrity partially on the Quality of Audit Results at the Inspectorate Office of Gorontalo Regency. 2. To determine the effect of Auditor Independence partially on the Quality of Audit Results at the Inspectorate Office of Gorontalo Regency. 3. To determine the effect of Auditor Ethics partially on the Quality of Audit Results at the Inspectorate Office of Gorontalo Regency, 4. To determine the effect of Auditor Integrity, Auditor Independence, Auditor Ethics simultaneously on the Quality of Audit Results at the Inspectorate Office of Gorontalo Regency. The subjects of this study were auditors working at the Inspectorate Office of Gorontalo Regency. The data collection method in this study used a questionnaire. This test was carried out using SPSS 21 and using the Method of Successive Interval (MSI). The data analysis techniques used to test the hypothesis were simple regression analysis and multiple regression analysis. Based on the results of the study, it can be concluded that the variables of Integrity, Independence, and Auditor Ethics have a positive and significant influence on the quality of Internal Audit at the Inspectorate Office of Gorontalo Regency, both partially and simultaneously.